Comparison of Plain X-ray and MRI Findings By Determining The Sensitivity and Specificity in the Diagnosis of Lumbar Spinal Stenosis (KYAMC Journal, 2021)
Background: Lumbar spinal stenosis is the most frequent indication for spine surgery. The X-ray and MRI are the choice of investigation. Justified use of radiography can be cost effective in the management of lumbar spinal stenosis.Objective: To evaluate and compare the sensitivity and specificity of the plain X-ray and MRI in the diagnosis of the lumbar spinal stenosis.Materials and Methods: A multicenter cross sectional analytical study was carried out from January 2014 to December 2015 on 70 patients of both sexes aged more than 25 years with chronic low back pain. Plain x-ray and MRI were done in all patients. The interval between plain x-ray and MRI was less than 3 months. A descriptive analysis was performed for all data.Results: The mean age (+ SD) was 45.1 (+ 5.4) years. Forty two (60%) were male and 28 (40%) were female. In plain x-ray of the lumbosacral spine, 30 (42.9%) had diskogenic spinal canal stenosis and 22 (31.4%) had both diskogenic and non diskogenic spinal canal stenosis. In the MRI, 35 (50.0%) cases had diskogenic spinal canal stenosis and 24 (34.3%) had both diskogenic and non diskogenic spinal canal stenosis. The validity of MRI evaluation for only diskogenic spinal canal stenosis was correlated, where the calculated values of plain x-ray were: sensitivity 80.0%, specificity 60.0%, accuracy 77.5%, positive predictive value 93.3% and negative predictive value 30.0%. The validity of MRI evaluation for both diskogenic and non diskogenic spinal canal stenosis was correlated, where the calculated values of plain x-ray were: sensitivity 83.3%, specificity 66.7%, accuracy 80.0%, positive predictive value 90.9% and negative predictive value 50.0%.Conclusion: Plain x-ray is a useful and reliable diagnostic modality for the evaluation, assessment and the subsequent appropriate management of lumbar spinal stenosis.KYAMC Journal. 2021;12(3): 161-165